2020
DOI: 10.3390/ijms21249677
|View full text |Cite
|
Sign up to set email alerts
|

c-Jun N-Terminal Kinase Inhibitors as Potential Leads for New Therapeutics for Alzheimer’s Diseases

Abstract: Alzheimer’s Disease (AD) is becoming more prevalent as the population lives longer. For individuals over 60 years of age, the prevalence of AD is estimated at 40.19% across the world. Regarding the cognitive decline caused by the disease, mitogen-activated protein kinases (MAPK) pathways such as the c-Jun N-terminal kinase (JNK) pathway are involved in the progressive loss of neurons and synapses, brain atrophy, and augmentation of the brain ventricles, being activated by synaptic dysfunction, oxidative stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 223 publications
(161 reference statements)
0
24
0
Order By: Relevance
“…AD is the most frequent neurodegenerative disorder, and is based on the aggregation of neurofibrillary tangles and Aβ peptide deposition in cortical and hippocampal neurons (reviewed in [ 55 ]). Aβ–JNK mechanisms attenuate the expression of antiapoptotic Bcl-2 genes, required for the apoptosis of cortical neurons that occur in AD progression [ 56 ].…”
Section: Jnk In Neurodegenerative Disordersmentioning
confidence: 99%
See 4 more Smart Citations
“…AD is the most frequent neurodegenerative disorder, and is based on the aggregation of neurofibrillary tangles and Aβ peptide deposition in cortical and hippocampal neurons (reviewed in [ 55 ]). Aβ–JNK mechanisms attenuate the expression of antiapoptotic Bcl-2 genes, required for the apoptosis of cortical neurons that occur in AD progression [ 56 ].…”
Section: Jnk In Neurodegenerative Disordersmentioning
confidence: 99%
“…JNK3 phosphorylated levels correlate with the progression of AD [ 58 , 59 ]. In vitro and in vivo models of AD have demonstrated that JNK knockout reduces synapse loss, Aβ depositions and neuronal cell death [ 54 , 55 , 60 ]. All together, these results indicate that JNK signalling plays a central role in AD neurodegeneration, but JNK also has emerged as a potential biomarker for early diagnosis, and a potential target to prevent neuronal cell death [ 55 ].…”
Section: Jnk In Neurodegenerative Disordersmentioning
confidence: 99%
See 3 more Smart Citations